Method for laser-assisted composite ultrasonic strengthening treatment of titanium alloy, product and application

The composite gradient nano-strengthening layer is prepared on the surface of titanium alloy through laser-assisted composite ultrasonic strengthening technology (LA-UNSM+USRP), which solves the problem that high-strength and high-strength steady-state strengthening layer is difficult to prepare on the surface of titanium alloy, and realizes the micro-moving of titanium alloy at high temperatures Significant performance improvement in fatigue.

CN119491180APending Publication Date: 2025-02-21TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411687858.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

It is difficult to prepare high-strength and high-strength steady-state surface reinforcement layers on the surface of titanium alloys, effectively preventing high-temperature micro-motion fatigue damage and improving the service life of titanium alloys.

Method used

Laser-assisted composite ultrasonic enhancement technology (LA-UNSM+USRP), combined with laser heating, ultrasonic nanosurface modification and ultrasonic surface rolling treatment technology, a composite gradient nanointensity layer is prepared to form a ceramic hardened layer and a nanoscale second phase. Introduce steady-state structure and residual compressive stress at large layers.

Benefits of technology

The rapid preparation of the steady-state composite gradient nanostrengthening layer on the surface of titanium alloy is realized, which significantly improves the high-temperature micro-moving fatigue resistance of titanium alloy, extends its service life, and breaks through the thermal mechanical stability of gradient nanostructures under high-temperature alternating loads. Sexual bottleneck.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119491180A_ABST
    Figure CN119491180A_ABST
Patent Text Reader

Abstract

The invention discloses a method for laser-assisted composite ultrasonic strengthening treatment of a titanium alloy, a product and application, and belongs to the technical field of metal material surface treatment.The method comprises the following steps that a composite gradient nanometer strengthening layer is prepared on the surface of the titanium alloy by combining laser with an ultrasonic nanometer surface modification and ultrasonic surface rolling treatment technology. The invention further provides the titanium alloy prepared through the method and application of the titanium alloy in the aviation field. According to the LA-UNSM + USRP technology, the surface damage of the titanium alloy is reduced, a stable composite gradient nanometer strengthening layer and a residual compressive stress field are provided, and the purpose of continuously and effectively improving the high-temperature fretting fatigue performance of the titanium alloy in the high-temperature fretting fatigue process of the titanium alloy can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of metal material surface treatment, and in particular relates to a method, product and application of laser-assisted composite ultrasonic strengthening treatment of titanium alloy. Background Art

[0002] Titanium alloy is an important material for manufacturing load-bearing components such as engine blades, blades, and fasteners in the aviation field. With the continuous development of science and technology, aircraft have put forward higher requirements for the durability of titanium alloy components under extreme service conditions such as high temperature alternating loads. Among them, the contact area of ​​the tenon and tenon groove of the titanium alloy blade of the aircraft engine is prone to high-temperature fretting fatigue. It is not only affected by high-temperature alternating loads, but also suffers from wear damage with a small displacement amplitude. Therefore, the damage to titanium alloy components is more complicated and harsh. However, titanium alloy has low hardness, poor thermal conductivity, high friction coefficient and notch sensitivity, and is very sensitive to high-temperature fretting fatigue damage. Therefore, how to effectively prevent high-temperature fretting fatigue damage and extend the service life of titanium alloy equipment has become a very important research proposition. In engineering practice, surface strengthening technologies such as shot peening are often used to reduce high-temperature fretting fatigue damage of components, but under the combined effects of wear, fatigue, and high temperature, work hardening is easily weakened, grain coarsening and residual compressive stress relaxation occur, affecting the effect of improving high-temperature fretting fatigue resistance. Therefore, how to prepare a high-strength and high-toughness steady-state surface strengthening layer on the surface of titanium alloy to solve the contradiction between high hardness and fretting wear resistance and high toughness and fatigue resistance at high temperature, and break through the bottleneck of poor stability of microstructure strengthening / stress strengthening under the coupling of high-temperature alternating loads, is the key to improving the high-temperature fretting fatigue resistance of titanium alloy, and it is also one of the key scientific problems that have long been urgently needed to be solved in the high-temperature service durability of titanium alloy.

[0003] Domestic and foreign researchers have carried out a lot of work on preparing high-strength and high-toughness strengthening layers on the surface of materials to improve the high-temperature fretting fatigue resistance of materials. Figure 1As shown in the figure, there are three main types of surface high-strength and high-toughness strengthening layer preparation methods that are most studied: 1) Surface mechanical strengthening methods that rely on stress fields (such as ultrasonic surface rolling strengthening, laser shock strengthening, etc.). However, when the plastic deformation ability of the material is poor, this method is difficult to introduce large fine grain strengthening, work hardening and residual compressive stress fields into the surface of the material. Therefore, it has limited effect on improving the anti-fretting fatigue performance of difficult-to-process metals such as titanium alloys. At the same time, this process is prone to weakening of work hardening, grain coarsening and relaxation of residual compressive stress under the combined effects of wear, fatigue and high temperature, which affects the effect of improving high-temperature fretting fatigue resistance; 2) Relying on temperature Surface modification methods using stress field (such as plasma nitriding, micro-arc oxidation, etc.), however, the ceramic layer prepared by this type of technology has poor toughness itself, which limits its role in stably improving the high-temperature fatigue resistance of titanium alloys; 3) "Two-step" surface strengthening methods that couple stress field and temperature field (such as surface mechanical grinding + nitriding, shot peening + micro-arc oxidation, etc.), however, this thermal coupling "two-step method" is prone to high temperature and long-term treatment during the preparation of the second step of the surface ceramic modified layer, which causes the gradient nanostructure prepared in the early stage to grow nanocrystals and relax residual compressive stress, thereby reducing and losing the advantage of improving the high-temperature micro-motion fatigue resistance of titanium alloys.

[0004] Therefore, it is necessary to further provide a titanium alloy surface treatment method that can improve the thermomechanical stability of the gradient nanostructure microstructure / residual compressive stress based on the thermal-mechanical coupling "two-step method" that effectively combines the advantages of the high hardness and wear resistance of the ceramic layer and the high toughness and fatigue resistance of the gradient nanostructure, to ensure that this high-strength and high-toughness composite gradient nano-modified layer continues to play a role in the high-temperature micro-fatigue process of the titanium alloy. Summary of the invention

[0005] In order to solve the above technical problems, the present invention proposes a method, product and application of laser-assisted composite ultrasonic strengthening treatment of titanium alloy.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A method for laser-assisted composite ultrasonic strengthening treatment of titanium alloys uses laser combined with ultrasonic nano surface modification and ultrasonic surface rolling treatment technology to prepare a composite gradient nano strengthening layer on the surface of the titanium alloy.

[0008] Beneficial effects: Based on the laser-assisted ultrasonic nano-surface modification technology (LA-UNSM) previously explored, Figure 2As shown, a laser-assisted composite ultrasonic strengthening technology (LA-UNSM+USRP) is proposed to prepare a titanium alloy with a steady-state composite gradient strengthening layer and resistance to high-temperature fretting fatigue. The present invention effectively combines the characteristics of rapid heating by continuous laser (LA), high strain rate of ultrasonic nano-surface modification (UNSM) and surface finishing by ultrasonic surface rolling treatment technology (USRP). Through the composite treatment of LA-UNSM+USRP technology, the surface damage of the titanium alloy is reduced, and a ceramic hardened layer and a second phase are quickly formed. At the same time, through the composite ultrasonic superposition treatment, a large-scale grain refinement and lattice distortion are caused, and a steady-state microstructure such as extremely small-sized nanocrystals and low-angle grain boundaries and a large layer of deep residual compressive stress are introduced to form a steady-state composite gradient nano-strengthening layer, which has both high-temperature fretting wear resistance and high-temperature fatigue resistance. At the same time, it can break through the bottleneck of poor thermomechanical stability of gradient nanostructure microstructure / residual compressive stress, ensure that the microstructure strengthening / stress strengthening under high-temperature alternating loads continues to play a beneficial role, and realize the improvement of high-temperature fretting fatigue resistance of titanium alloy materials.

[0009] Preferably, the diameter of the laser is 1-5 mm, and the power is 10-70 W.

[0010] Preferably, the static pressure is (30-50) N, the scanning speed is (250-1000) mm / min, the feed amount is (10-30) μm, and the amplitude is (20-30) μm.

[0011] Preferably, during the ultrasonic surface rolling treatment, the spindle speed is (60-120) r / min, the axial feed rate is (0.08-0.12) mm / r, the static pressure is (300-900) N, and the amplitude is (8-12) μm.

[0012] A titanium alloy prepared by a method for laser-assisted composite ultrasonic strengthening treatment of titanium alloy, wherein the surface of the titanium alloy comprises a ceramic film layer and a composite gradient nano-strengthening layer from the outside to the inside.

[0013] Beneficial effects:

[0014] Preferably, the ceramic film layer is an oxide / nitride ceramic layer including Al2O3, TiO2 and TiN.

[0015] Beneficial effects:

[0016] Preferably, the composite gradient nano-strengthening layer includes a very small size nanocrystalline layer, a nanocrystalline layer, an ultrafine crystal layer, a fine crystal layer and a coarse crystal layer from the outside to the inside. The term "outer" refers to a layer close to the ceramic film layer, and "inner" refers to a layer away from the ceramic film layer.

[0017] Preferably, the minimum grain size of the extremely small-sized nanocrystalline layer is 10 nm; and / or,

[0018] The nanocrystalline layer is 10-100 nm; and / or,

[0019] The ultrafine crystal layer is 100-500nm; and / or,

[0020] The fine crystal layer is 500-1000nm; and / or,

[0021] The coarse-grained layer is >1000nm.

[0022] Preferably, the thickness of the ceramic film layer is 5-10 μm; and / or,

[0023] The thickness of the extremely small-size nanocrystal layer is 5-10 μm; and / or,

[0024] The thickness of the nanocrystalline layer is 10-50 μm; and / or,

[0025] The thickness of the ultrafine crystal layer is 10-50 μm; and / or,

[0026] The thickness of the fine crystal layer is 50-100 μm; and / or,

[0027] The thickness of the coarse-grained layer is >100 μm.

[0028] The invention discloses an application of titanium alloy in the preparation of load-bearing components in the aviation field.

[0029] Compared with the prior art, the present invention has the following advantages and technical effects:

[0030] The present invention simultaneously utilizes the characteristics of local heating and cooling of lasers and local focusing of ultrasonic energy, and introduces thermomechanical energy to promote the diffusion, reconstruction, reaction and nucleation of elements and atoms in a short range under a relatively low temperature rise effect, thereby realizing the rapid preparation of ceramic hardened layers, nanoscale second phases and mixed gradient nanostructures; then, utilizing the characteristics of the large diameter of the rolling head of the USRP device and the ability to roll freely at 360°, under the action of a large amount of lubricating fluid, the furrowing effect and surface damage introduced during the LA-UNSM treatment process are repaired. At the same time, the subsequent USRP treatment can further refine the grains and introduce work hardening and lattice distortion, further generate extremely small-sized nanocrystals and low-angle grain boundaries in the mixed gradient nanostructure, and further stabilize and improve the thermomechanical stability of the microstructure / residual compressive stress of the material; the LA-UNSM+USRP technology in the present invention reduces the surface damage of the titanium alloy, provides a stable composite gradient nano-strengthening layer and residual compressive stress field, and can achieve the purpose of continuously and effectively improving the high-temperature micro-motion fatigue performance of the titanium alloy during the high-temperature micro-motion fatigue process of the titanium alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0032] Figure 1 It is a schematic diagram of the process of preparing a high-strength and high-toughness strengthening layer on a traditional metal surface;

[0033] Figure 2 This is a schematic diagram of the composite gradient nano-strengthening layer and high temperature fretting fatigue resistance constructed by LA-UNSM+USRP in Example 1 of the present invention;

[0034] Figure 3 This is a comparison diagram of the surface integrity of the steady-state composite gradient nano-reinforced layer obtained in Example 1 of the present invention and Comparative Example 3;

[0035] Figure 4 This is a comparison chart of the effects of different surface treatment states on high temperature fretting fatigue properties of titanium alloys according to an embodiment of the present invention. DETAILED DESCRIPTION

[0036] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0038] The embodiment of the present invention provides a method for laser-assisted composite ultrasonic strengthening treatment of titanium alloy, which utilizes laser combined with ultrasonic nano surface modification and ultrasonic surface rolling treatment technology to prepare a composite gradient nano strengthening layer on the surface of the titanium alloy.

[0039] In a preferred embodiment, the diameter of the laser is 1-5 mm, and the power is 10-70 W. If the laser diameter and power are higher than this range, surface ablation will occur, and if it is lower than this range, the laser will not provide sufficient power to soften the material.

[0040] In a preferred embodiment, during the ultrasonic nano-surface modification process, the static pressure is (30-50) N, the scanning speed is (250-1000) mm / min, the feed rate is (10-30) μm, and the amplitude is (20-30) μm. If the surface treatment is not performed under the above conditions, the surface plastic strain will be insufficient to produce a strengthening effect or the material surface will crack and fail due to too little or too much ultrasonic energy output.

[0041] In a preferred embodiment, during the ultrasonic surface rolling treatment, the spindle speed is (60-120) r / min, the axial feed rate is (0.08-0.12) mm / r, the static pressure is (300-900) N, and the amplitude is (8-12) μm. If the surface treatment is not performed under the above conditions, the ultrasonic rolling intensity and coverage will not match, which will reduce the surface roughness and strength.

[0042] A titanium alloy prepared by a method for laser-assisted composite ultrasonic strengthening treatment of titanium alloy, wherein the surface of the titanium alloy comprises a ceramic film layer and a composite gradient nano-strengthening layer from the outside to the inside.

[0043] In a preferred embodiment, the ceramic film layer is an oxide / nitride ceramic layer including Al2O3, TiO2 or TiN (mainly Al2O3, with a small amount of TiO2 and TiN).

[0044] In a preferred embodiment, the composite gradient nano-strengthening layer includes a very small size nanocrystalline layer, a nanocrystalline layer, an ultrafine crystal layer, a fine crystal layer and a coarse crystal layer from the outside to the inside. The term "outer" refers to a layer close to the ceramic film layer, and "inner" refers to a layer away from the ceramic film layer.

[0045] In a preferred embodiment, the minimum grain size of the extremely small-sized nanocrystalline layer is 10 nm; and / or,

[0046] The nanocrystalline layer is 10-100 nm; and / or,

[0047] The ultrafine crystal layer is 100-500nm; and / or,

[0048] The fine crystal layer is 500-1000nm; and / or,

[0049] The coarse-grained layer is >1000nm.

[0050] In a preferred embodiment, the thickness of the ceramic film layer is 5-10 μm; and / or,

[0051] The thickness of the extremely small-size nanocrystal layer is 5-10 μm; and / or,

[0052] The thickness of the nanocrystalline layer is 10-50 μm; and / or,

[0053] The thickness of the ultrafine crystal layer is 10-50 μm; and / or,

[0054] The thickness of the fine crystal layer is 50-100 μm; and / or,

[0055] The thickness of the coarse-grained layer is >100 μm.

[0056] The invention discloses an application of titanium alloy in the preparation of load-bearing components in the aviation field.

[0057] In a specific embodiment, the method steps of laser-assisted composite ultrasonic strengthening treatment of titanium alloy are as follows: (1) First, using LA-UNSM technology at a relatively low temperature (the highest temperature of the sample surface is lower than 350°C), a hard ceramic layer with a micron-level thickness and a gradient nanostructure containing a nanoscale second phase (the minimum grain size is about 50nm) are prepared on the surface of the titanium alloy. (2) Secondly, based on the LA-UNSM treatment, the surface of the titanium alloy is further treated by USRP technology to reduce surface damage, while further refining the grains to introduce extremely small-sized nanocrystals (about 10nm) and high-density low-angle grain boundaries to form a deep micron / millimeter-level residual compressive stress field. (3) After the LA-UNSM+USRP treatment successfully prepares a steady-state composite gradient strengthening layer on the surface of the titanium alloy, a specific median high-temperature fretting fatigue (HTFF) test is carried out (temperature 350°C, stress ratio R=-1, maximum alternating load 500MPa), and the fatigue life of the titanium alloy is increased by about 17 times, and its gradient nanostructure and residual compressive stress relaxation are small after HTFF fracture.

[0058] The laser used in the embodiment of the present invention is a YLR-200-mm-AC-Y11 fiber laser produced by IPG Optical Instruments, with a laser beam diameter of 1 to 5 mm and a laser power range of 10 to 70 W.

[0059] UNSM (ultrasonic nano-surface modification) is a technology that uses ultrasonic energy to process the surface of metal materials. The tool head processes the surface of the metal material, causing severe plastic deformation on the material surface and forming a metamorphic layer of a certain depth, thereby changing the surface microstructure, refining the surface grains and hardening the surface, and ultimately achieving the purpose of strengthening the material surface and improving the material's fatigue resistance. The tool head of the UNSM device in the embodiment of the present invention is hemispherical, has a small diameter, and cannot rotate freely, so the plastic strain introduced per unit area is high, and one UNSM treatment can form a gradient nanostructure on the surface of a material with high stacking fault energy.

[0060] USRP technology (ultrasonic surface rolling technology) is to process the surface of metal parts by combining ultrasonic impact energy and static load rolling. Specifically, the processing head applies a certain amplitude of ultrasonic frequency mechanical vibration along the normal direction of the workpiece surface, and under certain feeding conditions, the static pressure and ultrasonic impact vibration are transmitted to the surface of the rotating mechanical parts, producing an impact and extrusion effect, so that the metal material produces a large elastic-plastic deformation. After processing, the workpiece surface produces a certain elastic recovery, and the plastic flow fills or partially fills the "valley" on the workpiece surface with the "peak", thereby greatly reducing the surface roughness and improving the comprehensive performance index of its surface. In the USRP equipment used in the embodiment of the present invention, the tool head is a tungsten carbide ball with a diameter of 14mm, and the tungsten carbide ball can rotate freely at 360°. This greatly shares the role of ultrasonic impact, while reducing the accumulation of wear debris on the sample surface during the treatment process, and avoiding the generation of furrows on the sample surface while further refining the organization. In addition, during the USRP treatment process, lubricating oil is sprayed from the surface of the working ball head, the lubrication effect of the oil film is good, and the surface quality obtained is higher.

[0061] The composition of TC4 titanium alloy material is Ti-6Al-4V, which belongs to (α+β) type titanium alloy, with good comprehensive mechanical properties and high specific strength. The strength of TC4 is sb = 1.012GPa, and the density is g = 4.51g / cm 3 , specific strength sb / g=23.5, and the thermal conductivity of titanium alloy is low, the thermal conductivity of TC4 titanium alloy is l=7.955W / m·K.

[0062] Example 1

[0063] A method for laser-assisted composite ultrasonic strengthening of titanium alloy, such as Figure 2 As shown, the following steps are included:

[0064] (1) Pretreatment: TC4 titanium alloy was processed according to the standard "GB / T3075 Metal Axial Fatigue Test Method", and the working section of the fatigue specimen was rough turned and fine turned in turn, and then mechanically polished in the longitudinal direction to remove circumferential defects. The contact form between the micro-motion fatigue specimen and the micro-motion bridge was cylindrical-arc surface contact. The arc surface of the micro-motion pad was wire-cut electro-spark machined, and then ground with 400, 800, and 1200 sandpaper respectively to remove the heat-affected layer to obtain the titanium alloy specimen.

[0065] (2) LA-UNSM treatment: Use a laser to focus the laser beam on the front end of the UNSM equipment tool head, heat and soften the surface of the sample at the contact point between the tool head and the titanium alloy sample, where the heating temperature is 348.6°C, and then the tool head impact strengthens the heated part of the sample. Since the surface heating temperature of the titanium alloy sample is different under different laser powers, the strengthening effect of the combination of laser heating and UNSM is different, so the laser diameter and laser power suitable for matching UNSM are selected for the experiment. In this embodiment, the parameters of UNSM are: static pressure 50N, scanning speed 250mm / min, feed amount 10μm, amplitude 24μm; laser diameter is 3mm, and laser power is 56W.

[0066] (3) USRP treatment: The titanium alloy sample after LA-UNSM treatment in step (2) was further subjected to USRP treatment, wherein the USRP parameters were: spindle speed 60 r / min, axial feed 0.08 mm / r, static pressure 900 N, and amplitude 10 μm.

[0067] (4) Post-treatment: After the LA-UNSM+USRP test is completed, turn off the power supply, take out the sample, rinse the sample with running tap water to remove the residual lubricating liquid on the surface of the sample obtained in step (3), then blow dry with hot air and put it into a sample bag. At this point, the preparation of the steady-state composite gradient nano-reinforced layer is completed.

[0068] Upon further testing, Figure 2 As shown, the steady-state composite gradient nano-strengthening layer includes a ceramic film layer and a composite gradient nano-strengthening layer from the outside to the inside;

[0069] The ceramic film layer includes an oxide / nitride ceramic layer of Al2O3, TiO2 and TiN, with a thickness of 6 μm;

[0070] The composite gradient nano-strengthening layer includes an extremely small nanocrystalline layer, a nanocrystalline layer, an ultrafine crystal layer, a fine crystal layer and a coarse crystal layer from the outside to the inside. The minimum grain size of the extremely small nanocrystalline layer is 10nm, the average size of the nanocrystalline layer is 32nm, the ultrafine crystal layer is 113nm, the fine crystal layer is 574nm, and the coarse crystal layer is >1000nm; the thickness of the extremely small nanocrystalline layer is 10μm; the thickness of the nanocrystalline layer is 25μm; the thickness of the ultrafine crystal layer is 50μm; the thickness of the fine crystal layer is 50μm; and the inside is all coarse crystal layers.

[0071] Example 2

[0072] A method for laser-assisted composite ultrasonic strengthening treatment of titanium alloy, which is different from Example 1 only in that the parameters of UNSM in step (2) are: static pressure 30N, scanning speed 1000mm / min, feed amount 30μm, amplitude 10μm; laser diameter is 1mm, and laser power is 23W.

[0073] The USRP parameters in step (3) are: spindle speed 120 r / min, axial feed 0.12 mm / r, static pressure 300 N, and amplitude 8 μm.

[0074] Example 3

[0075] A method for laser-assisted composite ultrasonic strengthening treatment of titanium alloy, which is different from Example 1 only in that the parameters of UNSM in step (2) are: static pressure 40N, scanning speed 500mm / min, feed amount 20μm, amplitude 30μm; laser diameter is 5mm, and laser power is 68W.

[0076] The USRP parameters in step (3) are: spindle speed 100 r / min, axial feed 0.10 mm / r, static pressure 600 N, and amplitude 12 μm.

[0077] Comparative Example 1

[0078] A titanium alloy surface treatment method, which is different from Example 1 only in that step (2) is not included, and the titanium alloy is surface treated using only USRP technology. Other process steps and parameters are the same as those of Example 1.

[0079] Comparative Example 2

[0080] A titanium alloy surface treatment method, which is different from Example 1 only in that step (2) does not include laser treatment and step (3) is not included, that is, only UNSM technology is used to treat the titanium alloy surface, and specifically includes the following steps:

[0081] (1) Pretreatment: TC4 titanium alloy was processed according to the standard "GB / T3075 Metal Axial Fatigue Test Method", and the working section of the fatigue specimen was rough turned and fine turned in turn, and then mechanically polished in the longitudinal direction to remove circumferential defects. The contact form between the micro-motion fatigue specimen and the micro-motion bridge was cylindrical-arc surface contact. The arc surface of the micro-motion pad was wire-cut electro-spark machined, and then ground with 400, 800, and 1200 sandpaper respectively to remove the heat-affected layer to obtain the titanium alloy specimen.

[0082] (2) UNSM treatment: The UNSM equipment tool head is used to impact strengthen the sample. The parameters of UNSM are: static pressure 50N, scanning speed 250mm / min, feed amount 10μm, amplitude 24μm;

[0083] (3) Post-processing: After the test, turn off the power, take out the sample, rinse it with running tap water, blow it dry with hot air, and put it into a sample bag. At this point, the preparation of the steady-state composite gradient nano-reinforced layer is completed.

[0084] Comparative Example 3

[0085] A titanium alloy surface treatment method, which is different from Example 1 only in that step (3) is not included, and only the LA-UNSM technology is used to treat the titanium alloy surface. Other process steps and parameters are the same as those of Example 1.

[0086] Technical effect:

[0087] 1. Performance Characterization

[0088] Figure 3 This is a comparison chart of the surface integrity of the steady-state composite gradient nano-strengthening layer obtained in Example 1 of the present invention and Comparative Example 3. It can be seen that USRP effectively eliminates the furrows formed on the surface of LA-UNSM, and the sample surface is smoother and has fewer surface defects. At the same time, compared with the LA-UNSM sample, the ceramic layer distribution of the LA-UNSM+USRP sample is more uniform and continuous, without the phenomenon of peaks and troughs. In addition, compared with the LA-UNSM sample, the LA-UNSM+USRP treatment forms a gradient nanocrystalline layer with a finer layer depth and a larger hardened layer and introduces a larger hardened layer and residual compressive stress field.

[0089] 2. High temperature fretting fatigue test

[0090] High temperature micro-motion fatigue test was carried out on GPS-100 high frequency fatigue testing machine. The normal contact force was applied through the verification ring. According to the previous experimental research, the applied force was F = 2.04kN, and the peak pressure in the contact area was close to 196MPa. The maximum cyclic loading stress was σ max =500MPa, stress ratio R=-1, frequency f=127Hz, temperature is 350℃. The experimental results are as follows Figure 4 As shown in Figure 2, the median fatigue life of the untreated TC4 titanium alloy substrate sample under a maximum stress of 500 MPa is 5.99×10 4 Weekly.

[0091] After the TC4 titanium alloy samples were treated with USRP (Comparative Example 1), UNSM (Comparative Example 2) and LA-UNSM (Comparative Example 3), they were also subjected to high temperature fretting fatigue tests at 350°C and a maximum stress of 500 MPa. The median fatigue life was 7.63×10 4 , 15.89×10 4 and 66.31×10 4 Week. Figure 4 It can be seen that the median fatigue life of the steady-state composite gradient nano-strengthened layer specimen prepared by LA-UNSM+USRP treatment is increased to 102.95×10 4cycles, an increase of 17 times, and the gradient nanostructure and residual compressive stress relaxation after fracture are small, indicating that the steady-state composite gradient nano-strengthening layer prepared by LA-UNSM+USRP technology can significantly improve the high-temperature fretting fatigue resistance of titanium alloy. Figure 4 It can also be seen that the median fatigue life of the titanium alloy obtained in Example 1 of the present invention is much higher than the sum of the technical effects of Comparative Examples 1 and 3. Therefore, the LA-UNSM and USRP composite treatment method in the present invention has a certain synergistic effect, which greatly improves the high-temperature micro-fatigue resistance of the titanium alloy surface.

[0092] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A method for laser-assisted composite ultrasonic strengthening treatment of titanium alloy, characterized in that: A composite gradient nano-strengthening layer was prepared on the surface of titanium alloy by using laser combined with ultrasonic nano-surface modification and ultrasonic surface rolling treatment technology.

2. The method for laser-assisted composite ultrasonic strengthening treatment of titanium alloy according to claim 1, characterized in that: The diameter of the laser is 1-5 mm, and the power is 10-70 W.

3. The method for laser-assisted composite ultrasonic strengthening treatment of titanium alloy according to claim 1, characterized in that: During the ultrasonic nano-surface modification process, the static pressure is (30-50) N, the scanning speed is (250-1000) mm / min, the feed amount is (10-30) μm, and the amplitude is (20-30) μm.

4. The method for laser-assisted composite ultrasonic strengthening treatment of titanium alloy according to claim 1, characterized in that: During the ultrasonic surface rolling treatment, the spindle speed is (60-120) r / min, the axial feed rate is (0.08-0.12) mm / r, the static pressure is (300-900) N, and the amplitude is (8-12) μm.

5. A titanium alloy prepared by the method according to claim 1, characterized in that: The surface of the titanium alloy comprises a ceramic film layer and a composite gradient nano-strengthening layer from the outside to the inside.

6. The titanium alloy according to claim 5, characterized in that The ceramic film layer is an oxide / nitride ceramic layer including Al2O3, TiO2 and TiN.

7. The titanium alloy according to claim 5, characterized in that: The composite gradient nano-strengthening layer comprises, from the outside to the inside, an extremely small-size nano-crystalline layer, a nano-crystalline layer, an ultra-fine crystal layer, a fine crystal layer and a coarse crystal layer.

8. The titanium alloy according to claim 5, characterized in that: The minimum grain size of the extremely small-sized nanocrystal layer is 10 nm.

9. Use of the method according to any one of claims 1 to 4 or the titanium alloy according to any one of claims 5 to 8 in the preparation of load-bearing components in the aviation field.

Citation Information

Cited By

  • Heavy cutting type integral spindle box for horizontal turning center and manufacturing method

    CN122274677A

  • A heavy cutting type integral spindle box for a horizontal turning center and a manufacturing method thereof

    CN122274677B